Evaluation of leachate turbidity reduction in sanitary landfills following a coagulation/flocculation process enhanced by vegetable starch and thermal water - César Benavides; Sebastian Pacheco; Yeison Alberto Garcés Gómez; Fredy Edimer Hoyos (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This study evaluates the reduction of leachate turbidity in landfills after applying a mixture of banana starch and thermal water. Principal component analysis was applied to study the combined effect with four variables: pH, concentration of starch and thermal water mixture, rapid mixing speed and slow mixing speed. The experimental design involved 16 experiments with repetition in the jar test to obtain the optimum dose while measuring turbidity as a response variable. The results showed that after the oxidation process of organic matter, under optimal conditions determined in the experiment, the mixture of starch and thermal water contributed to the reduction of leachate turbidity by 29.1%.